Search 75,787 tutors
FIND TUTORS
Ask a question
0 0

what is -6 = 2/3z ?

Tutors, please sign in to answer this question.

3 Answers

-6=2/3z First, multiply both sides by 3z in order to get the z out of the denominator.

(3z)(-6)=(2/3z)(3z) this will cancel out the 3z on the bottom of the 2 leaving you with

(3z)(-6)=2 go ahead and simplify both sides which will give you

-18z=2 in order to get the z alone, you will divide both sides by -18

-18z/-18=2/-18 your -18 will cancel out, then reduce the fraction of 2/-18 your final answer is

z= -1/9

You want to get to z=, not 2/3 z.  

So the first step is to multiply by the inverse (the opposite) of 2/3z, which is 3/2z. 2/3 times 3/2 will give you 1 and that's what you want (1). 1z is the same as z.

The second step is to do the other side of the equation ( in this case the left) what was done to the right side of the equation; which is multiply by 3/2.  

When you multiply 3/2 times -6, your answer is -9.  z= -9. 

if this question is -6=2/3 z   Where z is in the numerator and not the denominator then multiply both sides of  the equation by 3/2. Z will equal -9